Konsep Digital Marketing Bakpia Juwara Satoe di Jogja yang Diimplementasikan ke Toko Kue Ende di Bengkulu - Nurmala, Una; Efendi, Marta Putri; Aprianti, Artia; Pratama, Areis Nanda; Maretha, Fevi (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adapt more effective and efficient marketing strategies, one of which is through digital marketing. This community service activity aims to increase the digital marketing capacity of Toko Kue Ende in Bengkulu by adapting the successful concept of Bakpia Juwara Satoe in Yogyakarta. The method used is Participatory Action Research (PAR), which emphasizes active collaboration between implementers and partners. Assistance is carried out in the form of training, improving digital content, SEO optimization strategies, simplifying ordering paths, and increasing advertising efficiency. The evaluation results showed an increase in website traffic of 65%, a conversion rate of 40%, a higher engagement rate, and ROAS efficiency. These findings confirm that the implementation of locally-based and participatory digital marketing can significantly increase the competitiveness of MSMEs.